FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN PENULARAN COVID-19 PADA KLASTER KELUARGA BERDASARKAN THEORY OF PLANNED BEHAVIOR - Saputri, Gita Ully; Indarjo, Sofwan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Cilacap Regency had 29,219 confirmed cases of COVID in September 2021. The household or family cluster is considered to be one of the most prominent transmitters of COVID-19 in Cilacap Regency, Central Java. Based on secondary data obtained, confirmed cases of COVID-19 in the work area of the UPTD Puskesmas Kroya I reached 860 cases with cases per cluster, namely the religious activities cluster 16 cases, the market cluster 23 cases, the boarding school cluster 86 cases, and the highest was the family cluster 85% (735 cases). This study aims to analyze the factors associated with COVID-19 transmission prevention behavior in the family cluster based on the Theory of Planned Behavior. This type of research is quantitative research with an observational analytic study design using a cross-sectional approach. The sample in the study was wives / housewives of adult age (20-60) years, sampling using cluster sampling technique with a total sample of 296 people. Data were collected using an instrument in the form of a questionnaire, data analysis was carried out, namely univariate analysis, bivariate using chi square test, and multivariate using regression test, data were analyzed using SPSS. The results showed that there was a relationship between attitude (p=0,024), subjective norm (p=0,003), perceived behavioral control (p=0,015) with intention. A relationship between attitude (p=0,008), subjective norm (p=0,000), perceived behavioral control (p=0,024), intention (p=0,000) with COVID-19 transmission prevention behavior. It is necessary to provide information related to COVID-19 to the family cluster in order to improve COVID-19 prevention behavior properly.